2016
DOI: 10.1038/srep36880
|View full text |Cite
|
Sign up to set email alerts
|

Fastest Formation Routes of Nanocarbons in Solution Plasma Processes

Abstract: Although solution-plasma processing enables room-temperature synthesis of nanocarbons, the underlying mechanisms are not well understood. We investigated the routes of solution-plasma-induced nanocarbon formation from hexane, hexadecane, cyclohexane, and benzene. The synthesis rate from benzene was the highest. However, the nanocarbons from linear molecules were more crystalline than those from ring molecules. Linear molecules decomposed into shorter olefins, whereas ring molecules were reconstructed in the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 88 publications
3
95
0
Order By: Relevance
“…Additionally, the prominent presence of C 6 radicals and C 6 H 6 molecules in our plasma growth process is likely important for increasing the growth rate and yield of GNSPs because graphene structures can be more effectively assembled from these molecules than from C 2 radicals. This notion is further corroborated by recent studies using solution plasmainduced formation of nano-carbons [60], which revealed that among hexane, hexadecane, cyclohexane and benzene, the synthesis rate from benzene was the highest.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, the prominent presence of C 6 radicals and C 6 H 6 molecules in our plasma growth process is likely important for increasing the growth rate and yield of GNSPs because graphene structures can be more effectively assembled from these molecules than from C 2 radicals. This notion is further corroborated by recent studies using solution plasmainduced formation of nano-carbons [60], which revealed that among hexane, hexadecane, cyclohexane and benzene, the synthesis rate from benzene was the highest.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, we attempted to synthesize Li‐doped carbon (Li‐C) using a process called solution plasma process (SPP) in which decomposition and polymerization of the solution components is accomplished by discharging a plasma in a solution. Using SPP, carbon materials have been synthesized from various carbon precursors, and the properties of the materials as well as their synthetic principles have been reported . These studies suggest that the carbon material obtained from a cyclic molecular precursor is formed directly at the interface between the plasma and the solution through intermediates such as benzene radical cations .…”
Section: Resultsmentioning
confidence: 99%
“…Using SPP, carbon materials have been synthesized from various carbon precursors, and the properties of the materials as well as their synthetic principles have been reported . These studies suggest that the carbon material obtained from a cyclic molecular precursor is formed directly at the interface between the plasma and the solution through intermediates such as benzene radical cations . Therefore, xylenes and cyclopentadienylithium were used as the carbon and Li precursors, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Morishita et al demonstrated the fast synthesis of nanocarbons by the SP process using benzene as a precursor, whereas the synthesis rate of nanocarbons by the SP process using hexane as a raw material was decreased by more than one order of magnitude. 25) Thus, the in SP process, it is very important to select suitable raw materials to control the synthesis rate of the nanocarbons. Moreover, the doping of different elements, such as B, 5) N, 26,27) F, 5) and Cl, 28) or multiple dopants 29,30) into the carbon matrix can be easily realized by the SP process using suitable organic solvents as raw materials.…”
Section: )mentioning
confidence: 99%